Late Permian to Late Triassic Large Igneous Provinces: Timing, Eruptive Style and Paleoenvironmental Perturbations - Boscaini, Andrea; Callegaro, Sara; Sun, Yadong; Marzoli, Andrea (Frontiers in Earth Science, 2022)
The emplacement of the Siberian Traps, the Central Atlantic Magmatic Province (CAMP) and the Wrangellia have been linked to end-Permian, end-Triassic mass extinctions, and to the Carnian Pluvial Episode (CPE), respectively. Exploring the timing, eruptive styles, and volatile degassing of these Large Igneous Provinces (LIPs) is crucial to understand their causal link to the catastrophic environmental crises that punctuated the Triassic. In this study we review the main characteristics of these LIPs, emphasizing common features and differences, and discussing aspects that are still in debate. Estimates of CO2 budgets and emissions from the three LIPs are based on the Nb content of little evolved basalts and highlight that early Siberian Traps and CAMP and high-Ti Wrangellia volcanics were quite CO2-rich. On the contrary, other volcanics from the three LIPs probably emitted relatively low amounts of CO2, which reinforces the possibility that thermogenic reactions between sills and sediments were additional fundamental suppliers of climate-modifying gases.